Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Influence of low-dosage hydrate inhibitors on methane clathrate hydrate formation and dissociation kinetics - Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (Energy Technology, 2015)
This work investigates the effect of low-dosage hydrate inhibitors (LDHIs) on methane hydrate formation and dissociation. The hydrate inhibitors used in this study were the sodium salt of polyacrylic acid, a polysaccharide chitosan, and the linear sulfated polysaccharide i-carrageenan; the inhibiting behavior of these additives were compared with that of the commonly used hydrate inhibitor polyvinylpyrrolidone for methane hydrate formation. A LDHI concentration of 1wt% was found to increase the induction time relative to that at a LDHI concentration of 0.1wt%. Chitosan was found to be better than the others in reducing nucleation and the growth rate of the hydrate at a concentration of 1wt%. At a lower concentration of 0.1wt%, nucleation inhibition was minimal, however, growth inhibition was significant. The effect of these inhibitors on the decomposition rate of the hydrate was also studied, and the decomposition kinetics at a constant driving force in excess of three-phase equilibrium is reported.
Keywords: gas uptake; hydrates; inhibitors; kinetics; thermal stimulation

Crystallization kinetics for carbon dioxide gas hydrate in fixed bed and stirred tank reactor - Kumar, Asheesh; Khatri, Dishant; Lee, Ju Dong; Kumar, Rajnish (Korean Journal of Chemical Engineering, 2016)
The phase change from germ nuclei to growth nuclei and subsequent volume transformation in a crystallization process was modeled by Avrami equations. The phase change during the hydrate formation was fitted with the classical Avrami model by utilizing gas uptake data. The idea is to understand the difference in growth behavior of hydrate crystals when in small pores compared to a stirred tank reactor which does not pose any physical restrictions to hydrate growth. The parameters n and k of the Avrami equation were determined explicitly for CO2 hydrate formation.
Keywords: Avrami Equation; CO2 Capture & Sequestration; Fixed Bed; Gas hydrates; kinetics

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel